Parametric synthesis of an electro-hydraulic executive device of a digital system of automatic control of a moving object - Aleksandrov, Eugene; Aleksandrova, Tetiana; Kostianyk, Iryna; Morgun, Yaroslav (Національний технічний університет "Харківський політехнічний інститут", 2022)
Most modern moving objects, including military moving objects, are equipped with guidance and stabilization systems with electro-hydraulic executive devices. Intercontinental ballistic missiles, space vehicles, aircraft, the main armament of tanks and ships have high-precision digital guidance and stabilization systems with electro-hydraulic actuators with potentiometric feedback, capable of ensuring high accuracy of stabilization of a moving object in a given direction. The work is devoted to the development of a methodology for selecting the value of the feedback channel amplification coefficient, which provides the maximum margin of stability and the maximum speed of the closed digital system of guidance and stabilization of a moving object. The proposed technique is based on the application of a discrete-continuous mathematical model of a closed digital system of guidance and stabilization of a moving object, which contains ordinary differential equations for describing the disturbed motion of the continuous part of the stabilized object, as well as difference equations for describing a discrete stabilizer. To construct the characteristic equation of a closed discrete system, the mathematical model is reduced to a system of difference equations using matrix series. At the same time, the number of considered members of the matrix series depends on the value of the quantization period of the digital stabilizer, therefore, in addition to determining the amplification coefficient of the feedback channel of the executive device, the proposed technique also includes the determination of the value of the quantization period of the digital stabilizer.

Більшість сучасних рухомих об'єктів, зокрема рухомих об'єктів військового призначення, оснащені системами наведення і стабілізації з електрогідравлічними виконавчими органами. Міжконтинентальні балістичні ракети, космічні апарати, літаки, основне озброєння танків і кораблів мають високоточні цифрові системи наведення і стабілізації з електрогідравлічними виконавчими елементами з потенціометричним зворотним зв'язком, здатними забезпечити високу точність стабілізації рухомого об'єкта щодо заданого напрямку. Робота присвячена розробці методики вибору значення коефіцієнта підсилення каналу зворотного зв'язку, що забезпечує максимальний запас стійкості і максимальну швидкодію замкненої цифрової системи наведення і стабілізації рухомого об'єкта. Запропонована методика базується на застосуванні дискретно-континуальної математичної моделі замкненої цифрової системи наведення і стабілізації рухомого об'єкта, що містить звичайні диференціальні рівняння для опису збуреного руху континуальної частини об’єкта, що стабілізується, а також різницеві рівняння для опису дискретного стабілізатора. Для побудови характеристичного рівняння замкненої дискретної системи математична модель приводиться до системи різницевих рівнянь із застосуванням матричних рядів. При цьому кількість врахованих членів матричних рядів залежить від величини періоду квантування цифрового стабілізатора, отже окрім визначення коефіцієнта підсилення каналу зворотного зв'язку виконавчого органу запропонована методика включає також визначення величини періоду квантування цифрового стабілізатора.
Параметричний синтез електрогідравлічного виконавчого органу цифрової системи автоматичного керування рухомим об'єктом
Keywords: guidance and stabilization system of a moving object; electrohydraulic executive device; quantization period of the digital stabilizer; margin of stability and speed of the closed-loop system; система наведення і стабілізації рухомого об'єкта; електрогідравлічний виконавчий орган; період квантування цифрового стабілізатора; запас стійкості і швидкодія замкненої системи